2019
DOI: 10.1002/jcc.26082
|View full text |Cite
|
Sign up to set email alerts
|

G‐Protein‐Coupled Receptor–Membrane Interactions Depend on the Receptor Activation State

Abstract: G‐protein‐coupled receptors (GPCRs) are the largest family of human membrane proteins and serve as primary targets of approximately one‐third of currently marketed drugs. In particular, adenosine A1 receptor (A1AR) is an important therapeutic target for treating cardiac ischemia–reperfusion injuries, neuropathic pain, and renal diseases. As a prototypical GPCR, the A1AR is located within a phospholipid membrane bilayer and transmits cellular signals by changing between different conformational states. It is im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 64 publications
0
29
0
1
Order By: Relevance
“…In the case of β2AR, it has been shown that zinc can also modulate the receptor, regulating orthosteric ligand binding or the effect of the agonist [ 49 , 50 ]. The role of lipids in GPCR function has been increasingly recognized, and simulations show their influence in receptor′s dynamics and activation [ 51 , 52 , 53 , 54 , 55 ]. In particular, cholesterol can not only modify physical properties of the membrane, but also directly bind to the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of β2AR, it has been shown that zinc can also modulate the receptor, regulating orthosteric ligand binding or the effect of the agonist [ 49 , 50 ]. The role of lipids in GPCR function has been increasingly recognized, and simulations show their influence in receptor′s dynamics and activation [ 51 , 52 , 53 , 54 , 55 ]. In particular, cholesterol can not only modify physical properties of the membrane, but also directly bind to the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, for the A 1 AR two inactive antagonist-bound structures [24,38] and a cryo-EM active agonist-bound structure [39] were released, so more reliable molecular modeling studies are now possible. Recently, GaMD investigated the flexibility profile of the active adenosine-bound and inactive PSB36-bound A 1 AR [97]. In both simulations, conformations of the ECL2 region and the intracellular end of TM6 fluctuated, with higher flexibility of these receptor portions and of the intracellular end of TM5 in the active state.…”
Section: Activation and Deactivationmentioning
confidence: 99%
“…Моделирование молекулярной динамики широко применяется для компьютерного конструирования лекарственных средств (CADD) [110,111]. Силовые поля для малых молекул имеют решающее значение, поскольку они не только являются элементами в процессе разработки силовых полей для более крупных биомолекул, но также представляют собой модельные соединения, которые переносятся в лиганды, используемые в CADD.…”
Section: метод молекулярной динамикиunclassified